Beyond the Textbook: Visualizing Knowledge for Enhanced Student Achievement - Almadani, Almadani; Novita, Mona; Sa’diyah, Halimatus (At-Tarbiyat, 2025)
This study investigates the effectiveness of audio-visual media in enhancing student motivation and understanding of abstract chemistry concepts. The research focuses on evaluating the impact of audio-visual media on the learning outcomes of 10th-grade science students. Employing a quantitative descriptive method with an ex post facto approach, this study examines students' perceptions of the learning media and its effects on motivation and comprehension without direct intervention. Data were collected through questionnaires, observations, and documentation, then analyzed using SPSS. Findings reveal a significant improvement in student learning outcomes, both in skills and knowledge, after using audio-visual media. Statistical tests show a substantial difference between pre-test and post-test scores, with a marked increase in the percentage of students meeting the minimum competency criteria. This study supports the Cognitive Theory of Multimedia Learning (CTML), which suggests that audio-visual learning facilitates deeper cognitive processing through dual-channel processing. The study’s implications indicate that audio-visual media not only enhances understanding of chemistry concepts but also reduces learning disparities among students. Integrating such media into the chemistry curriculum can offer a more interactive and comprehensive learning approach, especially for complex subjects.